Síndrome de donjuanismo: conceitos, medidas e correlatos - Moizéis, Heloísa Bárbara Cunha (2020)
This dissertation aimed to elaborate and test a measure to evaluate the dimensions that make up the Donjuanism syndrome, relating them to the dark personality traits, sexual compulsiveness and human values. To this end, three articles were prepared. In Article 1, of a theoretical nature, it was proposed to introduce the theme about this syndrome, which is characterized by a compulsion to win partners, which may be present in single and married people. Their characteristics, psychosocial consequences and their correlates were also presented. Article 2 dealt with the development of the Donjuanism Syndrome Scale (DJSS), gathering evidence of its psychometric properties. To this end, two studies were carried out with samples of university students. The present study aimed to develop the Donjuanism Syndrome Scale (DJSS). In study 1 (N = 215; Age = 22.6; 55.8% women), participants answered the Donjuanism Syndrome Scale and socio-demographic questions. An exploratory factor analysis indicated a pentafactorial structure, composed of 30 items, with adequate reliability. In Study 2 (N = 246; Age = 23.09; 54.9% female), the participants additionally answered the Tetrangular Love Scale (TLS). A confirmatory factor analysis corroborated the pentafactorial structure of the DJSS: betrayal (α = 0.81), disguised romanticism (α = 0.77), seduction (α = 0.72), affective instability (α = 0.70) and strategy conquest (α = 0.70), which correlated in the expected way with the factors of TLS (romantic passion, erotic passion, commitment and intimacy). Article 3, in turn, aimed at knowing to what extent the dark personality predicts Donjuanism syndrome, testing the mediating role of human values and sexual compulsiveness. 402 subjects (M= 22.63; SD = 5.83) from a Higher Education institution participated, who answered the Donjuanism Syndrome Scale, Sexual Compulsiveness Scale, Basic Values Questionnaire, Dark Triad Dozen and sociodemographic questions. The results suggested that the general factor of donjuanismo was explained by the factors that compose the dark personality, sexual compulsiveness and values of experimentation (R = 0,63; p < 0,001). Consequently, the effects of dark personality traits on Donjuanism syndrome, mediated by human values and sexual compulsiveness, were tested. In the sequence, direct and indirect effects of the traits were observed in relation to the donjuanism. Therefore, it is concluded that Donjuanism can be predicted by the dark traits, when mediated by the values of experimentation and sexual compulsiveness, and that the DJSS corresponds to an adequate tool for evaluating the dimensions of the Donjuanism syndrome, and its factors are related to the dark traits, sexual compulsiveness and value correlates.